2(x+y)+y-6+10y=

Simple and best practice solution for 2(x+y)+y-6+10y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+y)+y-6+10y= equation:


Simplifying
2(x + y) + y + -6 + 10y = 0
(x * 2 + y * 2) + y + -6 + 10y = 0
(2x + 2y) + y + -6 + 10y = 0

Reorder the terms:
-6 + 2x + 2y + y + 10y = 0

Combine like terms: 2y + y = 3y
-6 + 2x + 3y + 10y = 0

Combine like terms: 3y + 10y = 13y
-6 + 2x + 13y = 0

Solving
-6 + 2x + 13y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 2x + 6 + 13y = 0 + 6

Reorder the terms:
-6 + 6 + 2x + 13y = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 2x + 13y = 0 + 6
2x + 13y = 0 + 6

Combine like terms: 0 + 6 = 6
2x + 13y = 6

Add '-13y' to each side of the equation.
2x + 13y + -13y = 6 + -13y

Combine like terms: 13y + -13y = 0
2x + 0 = 6 + -13y
2x = 6 + -13y

Divide each side by '2'.
x = 3 + -6.5y

Simplifying
x = 3 + -6.5y

See similar equations:

| S-6=3-3 | | (4n-3)+(2n+5)= | | 0=x^5-6x^3+x | | 4(-4)-3y=-10 | | 6-6Z=-2(X+5) | | (79x-61y)(49x+5y)= | | 7a/10-3a/10 | | f(0)=1.25x | | 36/11=7/n | | 5(r+9)-5=p | | 0.3(d-100000)=202500 | | 2t+9=36 | | -4x+2x=8 | | 22=-4n+10 | | M-7=2-9 | | 500+115x= | | -7/2=-3/5y-7/3 | | -2=5+n/6 | | 9/2t=-1/9 | | 0.3(d-100000)=1000000 | | 3.5/0.2=n/1.3 | | 7p^2=-28p | | 20-10x-x^2=0 | | 6/25=d-30 | | 8-.8=f-14-2f | | 10=1/4x | | Y/67=-81-(-1262) | | (Y-4)(y^2-5y-2)= | | 10-8x=2(5+4x) | | 36-3r=18-6r | | f(2)=1.25x | | F=-3+2.5x+-1x^2 |

Equations solver categories